CHARACTERISTIC RELATIONSHIP OF LUNG TB LABORATORY OFFICER PUSKESMAS WITH ERROR RATE RESULTS OF SPUTUM EXAMINATION SUSPECTED PULMONARY TB IN KUDUS REGENCY - Retno Purbosari (Sean Institute, 2021)
English translation. The problem studied in this study is whether there is a relationship between the characteristics of lung tb laboratory officers puskesmas with the error rate of sputum examination results suspected pulmonary TB in Kudus Regency. The purpose of this study is to find out the relationship between the characteristics of lung tb laboratory officers with the error rate of sputum examination results of lung TB suspects in Kudus Regency. This type of research is explanatory reseach with a cross sectional approach. The free variables in the study were educational background, training, knowledge of direct microscopic sputum examination, staffing status, working life and workload while the bound variables were error rates. The population and samples in this study were all officers of the Tb Paru Puskesmas laboratory in Kudus Regency numbered 21 people. The instrument used is a questionnaire. Primary data is obtained through interviews. Secondary data is obtained from data in the Holy District Health Office. The data obtained is processed using the chi square test with an meaningful level (α) of 0.05. Based on the results of the study obtained that the characteristics of officers related to the error rate are training (p = 0.012, CC = 0.506), knowledge of direct microscopic examination of sputum (p = 0.004, CC = 0.594), staffing status (p = 0.025, CC = 0.484), working period (p = 0.004, CC = 0.594), and workload (p = 0.025, CC = 0.484). Based on the results of the research advice submitted is that training should be given to all tb laboratory officers of The Puskesmas lung on a regular basis every year because training is one of the efforts to improve the quality of human resources in terms of knowledge, attitudes and skills.